Clay sticks from the crude extract of Zingiber ottensii Valeton to inhibit the growth of Dermatophytes which are the cause of allergic rashes on the skin - Anan Scraggs; Ratchata Phromchaiwong; Tawanart Kanchanarochana; Nuttsinee Wongjiraheroun (Malaysia Journal of Invention and Innovation, 2024)
Athlete’s foot (Tinea pedis), Body ringworm (Tinea corporis), Jock itch (Tinea cruris), etc. These are diseases accumulated from fungi occurring on the skin, these types of fungi are classified in a group called Dermatophytes. At present, there are numerous options for treatment such as doctor appointments or using anti-fungal agents such as Clotrimazole of which when used for an extended amount of time can cause many side effects to the area of skin applied on such as rashes, hives, blisters etc. To provide an alternative, the project organizers have decided to study Zingiber ottensii Valeton’s fungal inhibition properties via crude extracts, due to it being easily found in the local area of Chiang Mai province and are cheap. Clay sticks being a popular form of skin care due to its compact and easy to carry nature makes it a perfect fit to make as a product from the crude extracts of Zingiber ottensii Valeton. The study shows that the crude extract from Zingiber ottensii Valeton showed anti-fungal properties and were effective in inhibiting the growth of Dermatophytes but weren’t as effective as the standard drug Clotrimazole. With that being said, the crude extracts of Zingiber ottensii Valeton were still suitable to make as a clay stick product.